2015
DOI: 10.1111/1460-6984.12207
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory investigation of communication management in residential‐aged care: a comparison of staff knowledge, documentation and observed resident–staff communication

Abstract: Resident-staff communication and communication management in residential-aged care is limited in scope and challenged in meeting residents' individual communication needs. Improvements in both documentation and staff knowledge of residents' communication needs are necessary. Strategies to facilitate communication with individual residents must be tailored, evidence based, documented in care plans and delivered to staff through ongoing education. Increased involvement of specialist providers such as speech path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
7
17
0
Order By: Relevance
“…However, in reality life‐story work requires little additional time and consideration needs to be given to what we prioritise, as the issue is not the amount of time available but how it is used (Bakken et al., ). This has to be considered in the context that aged care settings can often be task‐oriented thereby limiting opportunities to engage in meaningful conversations (Bennett, Ward, & Scarinci, ). However, life‐story work must be given greater importance (Bakken et al., ) especially in light of the fact that Dugmore, Orrell, and Spector () in their systematic review found that staff viewed psychological interventions including life‐story work, as not being “real work.”…”
Section: Discussionmentioning
confidence: 99%
“…However, in reality life‐story work requires little additional time and consideration needs to be given to what we prioritise, as the issue is not the amount of time available but how it is used (Bakken et al., ). This has to be considered in the context that aged care settings can often be task‐oriented thereby limiting opportunities to engage in meaningful conversations (Bennett, Ward, & Scarinci, ). However, life‐story work must be given greater importance (Bakken et al., ) especially in light of the fact that Dugmore, Orrell, and Spector () in their systematic review found that staff viewed psychological interventions including life‐story work, as not being “real work.”…”
Section: Discussionmentioning
confidence: 99%
“…In progressing CDC in this setting, communication between residents and care staff (resident–staff communication) will, therefore, be critical in achieving shared decision‐making and care planning. Existing studies, however, indicate resident–staff communication is largely task focussed with person‐centred and interpersonal communication for the purpose of getting to know the resident, understanding residents’ views, fostering residents’ sense of self and independence being far less common (Bennett, Ward, & Scarinci, ; Levy‐Storms, Claver, Gutierrez, & Curry, ; Savundranayagam, ). This communication dynamic exists between residents and staff despite aged care staff acknowledgement that effective resident–staff communication is critical to staff ability to develop positive relationships with residents and provide high quality, efficient, individualised care (Bennett, Ward, Scarinci, & Waite, ; Forsgren, Skott, Hartelius, & Saldert, ; Savundranayagam, Sibalija, & Scotchmer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Carers' interpersonal communication has been well-documented as an integral component of person-centred care. Notwithstanding the significance of non-verbal communication, verbal communication is extensively used in residential aged care as speech and conversational exchange (Bennett et al, 2016;Kristensen et al, 2017). Research has demonstrated the essential role of carers' person-centred communication for promoting dignity (Woolhead et al, 2006;Ostaszkiewicz et al, 2020), emotional support (Hafskjold et al, 2017) and personalised aged care (Hamiduzzaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated the essential role of carers' person-centred communication for promoting dignity (Woolhead et al, 2006;Ostaszkiewicz et al, 2020), emotional support (Hafskjold et al, 2017) and personalised aged care (Hamiduzzaman et al, 2020). Conversely, areas of concern regarding the management of verbal communication practices in aged care have been identified, including inadequate meaningful verbal communication (Bennett et al, 2016), a deprioritisation of social oriented conversation (Ludlow et al, 2020), a pressure on carers to complete tasks (Buckley, 2018) and limited interpersonal connection (Malins et al, 2004). such as the use of appropriate language or humour (Ostaszkiewicz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%